Copeptin and NT-proBNP for prediction of all-cause and cardiovascular death in ischemic stroke. (16th May 2017) - Tu, Wen-Jun; Ma, Guo-Zhao; Ni, Ying; Hu, Xia-Sheng; Luo, Ding-Zhen; Zeng, Xian-Wei; Liu, Qiang; Xu, Tingting; Yu, Lie; Wu, Boshui
Abstract : Objective: To evaluate long-term mortality in patients with acute ischemic stroke (AIS) by exploring the correlation between death and plasma concentrations of copeptin and N-terminal pro-B-type natriuretic peptide (NT-proBNP) in a cohort study. Methods: In a prospective, multicenter observational study of 4, 215 patients with AIS, copeptin and NT-proBNP levels were measured with a standardized method when patients were admitted to hospital. The primary endpoint was all-cause mortality or cardiovascular disease (CVD) mortality within 1 year. Results: During a follow-up period, 906 patients (20.1%, 95% confidence interval [CI] 18.9–21.2) died, including 589 cases of CVD mortality (13.1%, 95% CI 12.1–14.0). With the use of a multivariate analysis, both markers were found to have prognostic value in the same model (CVD mortality: odds ratio [OR] for fourth quartile of copeptin and NT-proBNP 1.68 and 2.58, 95% CI 1.22–2.49 and 1.76–4.05, respectively; all-cause mortality: OR for fourth quartile of copeptin and NT-proBNP 1.48 and 2.47, 95% CI 1.22–2.03 and 1.68–3.95, respectively). In a receiver operating characteristics analysis of CVD mortality, the area under the curve varied from 0.80 to 0.83 (95% CI 0.79–0.87) when the index of NT-proBNP was added and increased to 0.86 (95% CI 0.83–0.90) when both markers were added. Conclusions: Copeptin and NT-proBNP may be useful independent prognostic markers of all-cause or CVD mortality in Chinese patients with AIS.